The Phenomenon of Pragmatic Markers in Daily Conversations Among University Students - Nagamurali Eragamreddy (Institut Agama Islam Negeri Palopo, 2024)
This study explored pragmatic markers (PMs) used by college students in casual interactions. Understanding the prevalence, range, frequency, diversity, social context and functions of PMs, were the goals of the study. A qualitative descriptive method was used to examine nine student discussions. Participants were chosen at random from the Faculty of Education, Zuwila, Sebha University, Libya. Conversations in casual environments, such as residences and cafeterias, were discreetly recorded. PMs were found and grouped according to their function and social environment using thematic analysis. The results of the investigation showed that PMs were highly prevalent in all areas, including social interactions, agreement, and admiration. Pupils used a wide spectrum of PMs; the social milieu affected the frequency and variety of use. A greater variety of PMs were utilized in informal contexts for relationship development, emotional expression, and social navigation. The study's overall findings emphasize how important PMs are to student communication. These indicators are more than just filler words; they are vital resources that help students interact with others, communicate clearly, and form relationships. This study adds to a more comprehensive understanding of PM usage in regular student conversations.